2024
DOI: 10.14336/ad.2023.0823-3
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Microglia and Müller Glia in the Age-Related Macular Degeneration: Role and Therapeutic Value of Neuroinflammation

Abstract: Age-related macular degeneration (AMD) is a progressive neurodegeneration disease that causes photoreceptor demise and vision impairments. In AMD pathogenesis, the primary death of retinal neurons always leads to the activation of resident microglia. The migration of activated microglia to the ongoing retinal lesion and their morphological transformation from branching to ameboid-like are recognized as hallmarks of AMD pathogenesis. Activated microglia send signals to Müller cells and promote them to react cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 187 publications
0
4
0
Order By: Relevance
“…(Zhao et al, 2023). In addition, the crosstalk between microglia, Müller glia and astrocyte plays an important role in AMD pathology process (Cuenca et al, 2014;Zhao et al, 2023). In this study, cell-cell communication analysis showed that Müller glia and astrocyte interact with microglia via secreted SPP1.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…(Zhao et al, 2023). In addition, the crosstalk between microglia, Müller glia and astrocyte plays an important role in AMD pathology process (Cuenca et al, 2014;Zhao et al, 2023). In this study, cell-cell communication analysis showed that Müller glia and astrocyte interact with microglia via secreted SPP1.…”
Section: Discussionmentioning
confidence: 70%
“…Currently, microglia, as one type of neuroglial cells, have been found to closely interact with other cells in both central and peripheral nervous system, which is important for the maintenance of nervous tissues. Notably, it has been suggested that the migration of activated microglia to the ongoing retinal lesion and their phenotype transformation are the hallmarks of AMD pathogenesis ( Zhao et al, 2023 ). In addition, the crosstalk between microglia, Müller glia and astrocyte plays an important role in AMD pathology process ( Cuenca et al, 2014 ; Zhao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations